RGD-independent cell adhesion to the carboxy-terminal heparin-binding fragment of fibronectin involves heparin-dependent and -independent activities (The Rockefeller University Press, 1990)
Cell adhesion to extracellular matrix components such as fibronectin has a complex basis, involving multiple determinants on the molecule that react with discrete cell surface macromolecules. Our previous results have demonstrated that normal and transformed cells adhere and spread on a 33-kD heparin binding fragment that originates from the carboxy-terminal end of particular isoforms (A-chains) of human fibronectin. This fragment promotes melanoma adhesion and spreading in an arginyl-glycyl-aspartyl-serine (RGDS) independent manner, suggesting that cell adhesion to this region of fibronectin is independent of the typical RGD/integrin-mediated binding. Two synthetic peptides from this region of fibronectin were recently identified that bound [3H]heparin in a solid-phase assay and promoted the adhesion and spreading of melanoma cells (McCarthy, J. B., M. K. Chelberg, D. J. Mickelson, and L. T. Furcht. 1988. Biochemistry. 27:1380-1388). The current studies further define the cell adhesion and heparin binding properties of one of these synthetic peptides. This peptide, termed peptide I, has the sequence YEKPGSP-PREVVPRPRPGV and represents residues 1906-1924 of human plasma fibronectin. In addition to promoting RGD-independent melanoma adhesion and spreading in a concentration-dependent manner, this peptide significantly inhibited cell adhesion to the 33-kD fragment or intact fibronectin. Polyclonal antibodies generated against peptide I also significantly inhibited cell adhesion to the peptide, to the 33-kD fragment, but had minimal effect on melanoma adhesion to fibronectin. Anti-peptide I antibodies also partially inhibited [3H]heparin binding to fibronectin, suggesting that peptide I represents a major heparin binding domain on the intact molecule. The cell adhesion activity of another peptide from the 33-kD fragment, termed CS1 (Humphries, M. J., A. Komoriya, S. K. Akiyama, K. Olden, and K. M. Yamada. 1987. J. Biol. Chem., 262:6886-6892) was contrasted with peptide I. Whereas both peptides promoted RGD-independent cell adhesion, peptide CS1 failed to bind heparin, and exogenous peptide CS1 failed to inhibit peptide I-mediated cell adhesion. The results demonstrate a role for distinct heparin-dependent and -independent cell adhesion determinants on the 33-kD fragment, neither of which are related to the RGD-dependent integrin interaction with fibronectin.